2005
DOI: 10.1111/j.1749-6632.2005.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Neuroprotective Pathways by Metabotropic Group I Glutamate Receptors: A Potential Target for Drug Discovery?

Abstract: Stroke neuroprotection trials suggest that pharmacological manipulations of a single neuroprotective mechanism are generally ineffective and that new approaches, possibly involving simultaneous manipulations of multiple mechanisms, need to be sought. To identify optimal components for such a multipronged approach, we studied NMDA receptor activation‐induced cell death in organotypic hippocampal culture preparations as a model of excitotoxicity. Metabotropic group I glutamate receptor (mGluR) activation by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Our results indicate that the excitotoxic potential of AMPA and NMDA receptor agonists was reduced in preconditioned slices; this is in accord with reports showing that cortical cultures preconditioned with KCN (McLaughlin et al ., 2003) or organotypic hippocampal slices preconditioned with DHPG (Blaabjerg et al ., 2003) are protected against NMDA excitotoxicity. The reduced NMDA response after preconditioning stimuli has been associated with caspase 3 activation and increased production of neuroprotective proteins such as HSP 70 (McLaughlin et al ., 2003) or with Rab5b‐stimulated endocytosis of NMDA receptors (Baskys et al ., 2005). Similarly, ischemic preconditioning confers neuroprotection against global ischemia in vivo by attenuating the postischemic modifications in subunit composition that lead to the formation of Ca 2+ ‐permeable AMPA receptors (Tanaka et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that the excitotoxic potential of AMPA and NMDA receptor agonists was reduced in preconditioned slices; this is in accord with reports showing that cortical cultures preconditioned with KCN (McLaughlin et al ., 2003) or organotypic hippocampal slices preconditioned with DHPG (Blaabjerg et al ., 2003) are protected against NMDA excitotoxicity. The reduced NMDA response after preconditioning stimuli has been associated with caspase 3 activation and increased production of neuroprotective proteins such as HSP 70 (McLaughlin et al ., 2003) or with Rab5b‐stimulated endocytosis of NMDA receptors (Baskys et al ., 2005). Similarly, ischemic preconditioning confers neuroprotection against global ischemia in vivo by attenuating the postischemic modifications in subunit composition that lead to the formation of Ca 2+ ‐permeable AMPA receptors (Tanaka et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms leading to an increased neuronal resistance to ischemic injury (a phenomenon known as ischemic preconditioning or ischemic tolerance) are still not clearly understood and a number of possible induction pathways, including activation of glutamate receptors and changes in the concentration of intracellular free Ca 2+ , have been proposed (Dirnagl et al ., 2003; Bickler & Fahlman, 2004; Gidday, 2006). Recently, it has been demonstrated that brief activation of group I metabotropic glutamate (mGlu) receptors (consisting of mGlu1 and mGlu5 receptor subtypes) with the selective agonist (S)‐3,5‐dihydroxyphenylglycine (DHPG) reduces NMDA‐mediated Ca 2+ inflow and the resulting cell death, suggesting that activation of these mGlu subtypes may contribute to the induction of tolerance towards excitotoxic events (Blaabjerg et al ., 2003; Baskys et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate that the negative regulation of synaptic function seen after mGluR activation in the mature nervous systems involves mechanisms like LTD, receptor endocytosis and induction of glutamate transporters, but during development in a related scenario has more pronounced effects and acts on dendritic growth. In both cases the negative action of mGluR is likely to be neuroprotective by limiting the excitotoxic effect of glutamate release (Baskys et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This type of NR1 expression during degeneration has been reported in CA1 neurons destined to die following subarachnoid hemorrhage (Bendel et al, 2005). However, due to the overstimulation caused by capsaicin, translated NMDA receptors may fail to enter the plasma membrane or may be internalized and degraded more rapidly (Baskys et al, 2005;Bendel et al, 2005;Wu et al, 2005), preventing detection of the protein by IF. Second, there have been several reports of increased NMDA expression and activity in the dorsal horn following peripheral nerve damage (Zou et al, 2000;Caudle et al, 2003;Song et al, 2003;Gao et al, 2005;Roh et al, 2008a,b;Suckow and Caudle, 2009).…”
Section: Discussionmentioning
confidence: 94%